The Effect of Coffee Compsumption on Superoxide Dismutase (SOD) Enzyme Expression in Wistar Rats Induced by Hyper LDL - Rendra Chriestedy Prasetya; Nadie Fatimatuzzahro (Health Notions, 2020)
One of the causes of stroke is atherosclerosis. The incidence of occurrence ischemic stroke caused by atherosclerosis is 95%. Atherosclerosis is caused by oxidative stress in the endothelium due to the formation of Reactive Oxygen Species (ROS). Hyperlipidemia (hyper LDL) is one of the risk factors of elevated ROS. One of the enzymes that play a role in preventing the formation of ROS is superoxide dismutase (SOD). Coffee has a powerful antioxidant in which one of its active ingredients is chlorogenic acid that capable to inhibiting ROS formation. Fifteen wistar male divided into 3 groups. Group I (Control) were given standard fed, Group II (Hyperlipidemia) were given standart fed and hyperlipid diet, Group III (Coffee) were given standart fed and hyperlipid diet + coffee consumption. Treatment were done everyday for 30 days. Blood serum in each group was taken on day 30 and examined by ELISA superoxide dismutase (SOD). The results showed that superoxide dismutase levels in coffee group was significantly higher than hyperlipidemia group (p = 0,006). This study proves that coffee consumption can increase the production of superoxide dismutase enzyme. Keywords: atherosclerosis; coffee; hyperlipid; SOD